2017
DOI: 10.1002/admi.201601237
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ultrathin Amorphous ALD Alumina and Titania on the Rate Capability of Anatase TiO2 and LiMn2O4 Lithium Ion Battery Electrodes

Abstract: Interface modification is a heavily investigated method of extending the lifetime of lithium ion batteries. While many studies have explored the effect of interface coating on the lifetime, the rate capability is often overlooked. In this study, the authors investigated the influence of ultrathin (<10 nm) atomic layer deposition (ALD) coatings of amorphous Al2O3 and amorphous TiO2. It is found that, on thin‐film anatase TiO2, the rate capability is unaffected by an amorphous TiO2 coating since it does not pose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 74 publications
(80 reference statements)
2
58
0
Order By: Relevance
“…As for coating approaches, the ALD, in sharp comparison with the conventional mechanical mixing and sol-gel methods, affords extraordinary homogeneous cladding layer on the surface with precisely regulated down to sub-nanometers levels [ 5 , 164 ]. In this part, we comprehensively summarize the surface engineering via the ALD for cathode materials including layered cathodes, such as LiCoO 2 [ 111 , 112 , 118 , 148 , 149 ], LiNi x Mn y Co z O 2 [ 113 , 114 , 119 , 154 , 155 , 156 , 157 ], and Li-rich x Li 2 MnO 3 ·(1 − x )LiMO 2 (M = Mn, Ni, Co) [ 161 , 162 , 163 ], and spinel cathodes, such as LiMn 2 O 4 [ 150 , 151 , 152 , 153 ] and LiNi 0.5 Mn 1.5 O 4 [ 52 , 158 , 159 , 160 ], as listed in Table 3 . After careful observation in Table 3 , we can discover that the compounds serving as ALD coating layer for cathode materials can be mainly divided into four categories: metal oxides (Al 2 O 3 [ 118 , 119 , 152 , 154 , 155 , 156 , 159 , 161 , 163 , 165 , 166 ], TiO 2 ...…”
Section: Sur-/interfacial Engineering Optimization Via the Aldmentioning
confidence: 99%
“…As for coating approaches, the ALD, in sharp comparison with the conventional mechanical mixing and sol-gel methods, affords extraordinary homogeneous cladding layer on the surface with precisely regulated down to sub-nanometers levels [ 5 , 164 ]. In this part, we comprehensively summarize the surface engineering via the ALD for cathode materials including layered cathodes, such as LiCoO 2 [ 111 , 112 , 118 , 148 , 149 ], LiNi x Mn y Co z O 2 [ 113 , 114 , 119 , 154 , 155 , 156 , 157 ], and Li-rich x Li 2 MnO 3 ·(1 − x )LiMO 2 (M = Mn, Ni, Co) [ 161 , 162 , 163 ], and spinel cathodes, such as LiMn 2 O 4 [ 150 , 151 , 152 , 153 ] and LiNi 0.5 Mn 1.5 O 4 [ 52 , 158 , 159 , 160 ], as listed in Table 3 . After careful observation in Table 3 , we can discover that the compounds serving as ALD coating layer for cathode materials can be mainly divided into four categories: metal oxides (Al 2 O 3 [ 118 , 119 , 152 , 154 , 155 , 156 , 159 , 161 , 163 , 165 , 166 ], TiO 2 ...…”
Section: Sur-/interfacial Engineering Optimization Via the Aldmentioning
confidence: 99%
“…The results showed that the surface coating materials exhibited improved rate capability. 22 Laskar et al prepared MgO-coated Li[Ni 0.5 Mn 0.3 Co 0.2 ]O 2 (NMC) cathode by atomic layer deposition method. The results showed that cyclic performance was signicantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Although the capacities of other coated samples are inferior to 20‐ALD‐NG, they are still higher and more stable than bare NG. Thus, it can be speculated that the appropriate ALD coating has a beneficial effect on K + storage, but the too thick Al 2 O 3 layer oppositely increases the resistivity of K ions …”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be speculated that the appropriate ALD coating has a beneficial effect on K + storage, but the too thick Al 2 O 3 layer oppositely increases the resistivity of K ions. 35 CV analysis was utilized to verify the mechanism of K + intercalation/deintercalation in 20-ALD-NG, 50-ALD-NG, and NG. The scan rate is 1 mV s −1 , and the scan voltage range from 0.01 to 3.00 V. Figure 4A is associated with the intercalation of K + into graphite and the formation of KC 8 .…”
Section: Resultsmentioning
confidence: 99%